Iraqi Schools in the Islamic Eras and Their Impact on Social Structure - Al-Himyari, Asst Prof. Dr. Muhammad Riyad Hamed Al-Himyari; Al-Kaldari, Asst.L. Raouf Abdul Razzaq Nouri Al-Kaldari (Sulaimani Journal for Humanities, 2026)
Iraqi schools during the Islamic eras were among the most prominent educational institutions that contributed to societal development. These schools served as beacons of knowledge and enlightenment, playing a vital role in shaping the Islamic community by nurturing minds and instilling values and principles. Schools first appeared in Iraq during the Abbasid era and spread widely in various cities such as Baghdad, Kufa, and Basra. They focused on teaching religious, linguistic, literary, and philosophical sciences, along with applied sciences like medicine, engineering, and astronomy. These schools created a fertile scientific environment that encouraged research and innovation, leading to the emergence of many scholars and thinkers. Iraqi schools played a crucial role in forming educated elites who led society and guided its cultural and civilizational progress. Through these institutions, knowledge and culture spread across different social classes, raising public awareness and strengthening social cohesion by providing spaces for interaction and exchange of ideas among various groups. One of their most significant outcomes was the preservation of Islamic identity by teaching religious sciences and reinforcing noble values that even influenced other civilizations. Notable examples of these schools include the Kufan, Basran, Nizamiyya, and Mustansiriyya schools.
Keywords: school; Islamic era; civilization; social structure